Two-phonon structure of the neutron-rich nuclei. (December 2020) - Severyukhin, A.P.; Arsenyev, N.N.; Testov, D.
Abstract: Starting from the Skyrme energy-density functional, the microscopic model of the spin-isospin excitations is developed for the β -delayed γ -spectroscopy. We take into account the coupling between one- and two-phonon terms in the wave functions of 1 + states of daughter nuclei. An extension of the two-phonon space allowing for the additional charge-exchange phonons substantially enriches the 1 + spectrum. As an example, the β -decay rates of neutron-rich nuclei 126, 128 Cd are discussed.